Pengembangan E-Modul Matematika Model Flipped Classroom pada Pembelajaran untuk Meningkatkan Kemampuan Komunikasi Matematis - Danuri Danuri; Aunora Sukma Choirunisa (Universitas Sarjanawiyata Tamansiswa, 2023)
The goals of this study are to: 1) design a math e-module appropriate for fifth graders; 2) establish whether or not students in that grade level are qualified to take advantage of the module; and 3) evaluate the module's efficacy. Examine the effect that the aforementioned Mathematics e-Module has had on fifth graders' capacity to articulate mathematical concepts. The research was conducted during the 2022–2023 school year at First Kadipiro Elementary School in Bantul, Yogyakarta. The ultimate purpose of this research is to provide a useful contribution to ADDIE's overall framework (Analysis, Design, Development, Implementation, and Evaluation). Twenty-four kids in the fifth grade were selected at random to participate in this study. The results of the study revealed the following: 1) The ADDIE paradigm was used throughout the creation of the mathematics e-module. The media expert is excellently competent, the teacher and student surveys yielded good results, and the expert review of the material all weighed in favor of implementing the mathematics e-module. The Paired Sample T-Test indicates that the Mathematics e-Module is effective and that there is a statistically significant improvement in test scores after completing the module compared to before. Four) Students' mathematical communication improves as a result of using the Mathematical e-Modul. The 70.1589.63 point increase in average grade between the pre-and post-tests is indicative of this.